The Influence of EFL Teachers’ Hope and Trust on Their Academic Grit: A Theoretical Review - Xu, Yushu (Frontiers in Psychology, 2022)
The role of emotions in second/foreign language education has been exponentially highlighted in the literature. However, the interplay of EFL teachers’ hope, trust, and grit has witness a scant attention among L2 researchers. Against this shortcoming, the present mini-review article made an effort to offer a theoretical analysis of the theoretical and empirical underpinnings of these three constructs. In so doing, it presented the definitions, conceptualizations, dimensions, theories, related studies, and the way these variables can influence one another. Drawing on scientific findings in the literature, this study proposed some implications for EFL teachers, teacher trainers, principals, and scholars to enhance their knowledge of psycho-emotional factors and how establishing an environment based on hope and trust can generate success in L2 education. Finally, some recommendations for future research are made to drive this line of research forward.